Treatment of multibacillary leprosy following the development of dapsone hypersensitivity syndrome - Sudarsono, Sudarsono (UI Scholars Hub, 2019)
Background: World Health Organization (WHO) multi-drug therapy (MDT) is the current standard treatment for leprosy. A wide range of frequency of adverse effects caused by MDT has been reported. Dapsone hypersensitivity syndrome (DHS) is a serious adverse effect caused by dapsone. Prompt withdrawal of dapsone is important aspect in the management of DHS. Alternative regimens are needed to treat leprosy patient with DHS. Case Illustration: A 37-year-old man with multibacillary (MB) leprosy developed DHS in 39 days after the initiation of WHO MDT. Dapsone was withdrawn and methylprednisolone of 75 mg/day was prescribed. Twelve days after admission the patient showed clinical and laboratory improvement and was discharged. Treatment for multibacillary leprosy was continued with rifampicin and clofazimine with standard dosage. The bacterial index (BI) and morphological index (MI) showed +1 and 0 respectively in one month after the completion of 12 pulses of modified MB-MDT. Discussion: In the event of severe dapsone toxicity like DHS, WHO recommends that no modification to MDT is required other than immediately stopping dapsone in the case of those receiving MB-MDT. Multiple doses of rifampicin, ofloxacin and minocycline (ROM) therapy can be used as another alternative in leprosy patient with severe adverse effect while taking dapsone. Conclusion: Combination of rifampicin and clofazimine may be effective in treating MB leprosy with dapsone toxicity.